The factors that affect career choice among high school students in Marondera district - Chimombe, Tinashe (Midlands State University, 2017)
The study explored the personal, school, family, peer and community factors that affect the career choice of high school students in Marondera District. There is no clear process on career choice decisions and hence little is known about the factors that influence career choice among high school students in Zimbabwe. A positivism approach was utilized in the study .A descriptive survey research design was employed and questionnaires were used to collect data. A two stage cluster sampling was used to select the participants utilizing probability disproportionate method to get the 210 participants from the five clusters. Response percentages, frequencies and figures were used to present the finding Results showed that personal, school and family factors had a moderate to high influence on the participants’ career choice. The present study needs to be replicated with a larger sample drawn from a very big population sample and high school students from different provinces for generalizability of the findings. The participants made their career choices later in their life at different ages. The researcher recommended that parents need to understand and respect their children’s career choices as career choice is innate and be educated so that they can help their students in making the right career choice as the participants trust them.